In Vivo Anticancer Evaluation of Neferine from Nelumbo nucifera in Ehrlich Ascites Carcinoma-Bearing Mice - Batchu, Sravani; E, Bhavya; Darwin, C. Ronald (Journal of Neonatal Surgery, 2025)
The current study reports the isolation and in vivo anticancer evaluation of neferine, a bisbenzylisoquinoline alkaloid, extracted from Nelumbo nucifera seeds. Neferine was purified through solvent extraction and chromatographic separation using a mixture of chloroform, methanol, and ammonium hydroxide (95:4.5:0.5), resulting in a nearly pure fraction. The antitumour activity of neferine was assessed in Ehrlich Ascites Carcinoma (EAC)-bearing mice, evaluating body weight, haematological parameters, mean survival time (MST), and percentage increase in life span (% ILS). Mice treated with neferine showed dose-dependent antitumour activity, with significant reductions in body weight and tumour burden observed at higher doses (75–150 mg/kg). At 100 mg/kg and above, neferine demonstrated comparable efficacy to 5-Fluorouracil in reducing tumour burden while exhibiting a favourable safety profile, as indicated by lower body weight loss. Neferine also modulated haematological parameters, increasing haemoglobin and red blood cell counts while reducing white blood cell counts and neutrophil levels. These improvements correlated with reduced tumour-induced inflammation and enhanced immune function. Furthermore, neferine extended the MST and % ILS of EAC-bearing mice, with the highest dose (150 mg/kg) resulting in a 64.25% increase in life span, closely matching the efficacy of 5-Fluorouracil. These findings suggest that neferine holds promise as a potential anticancer agent, warranting further investigation for its clinical application.